Evolution of nutrient availability in maturation phase of composting using proportions of different residues inoculated with Beijerinckia indica - Lusiene Barbosa Sousa; Newton Pereira Stamford; Wagner Silva Oliveira; Emmanuella Vila Nova Silva; Marllon dos Santos Martins; Carolina Etienne Rosália e Silva Santos (Acta Scientiarum. Agronomy, 2018)
Organic matter has low N content; however, organic matter may be enriched by inoculation with selected diazotrophic bacteria. The aim of the paper was to evaluate the effects of biofertilizer produced by mixing different types and proportions of organic matter inoculated with the diazotrophic bacteria Beijerinckia indica. The experiment consisted of plastic trays (6 L) containing 5 kg of three different types of organic matter (filter mud cake, earthworm compost, and crop residue) applied in the following proportions (v:v:v): 1-(5:0:0), 2-(4:1:0), 3-(4:0:1), 4-(3:2:0), 5-(3:1:1), 6-(3:0:2), 7-(2:3:0), 8-(2:2:1), 9-(2:1:2), 10-(2:0:3), 11-(1:4:0), 12-(1:3:1), 13-(1:2:2), 14-(1:1:3), 15-(1:0:4), 16-(0:5:0), 17-(0:4:1), 18-(0:1:4), 19-(0:3:2), 20-(0:2:3), and 21-(0:0:5). Samples were collected following inoculation with B. indica at 0, 10, 20, 30, and 40 days of the maturation phase. The chemical analyses were: pH (H2O), total C and N, available P and K, and exchangeable Na+, Ca+2, Mg+2. The treatments with the best results showed significant effects following the maturation phase. The exceptions were C and N, which presented only individual effects. In general, the organic matter proportions (5:0:0), (3:2:0), and (2:3:0) resulted in a significant increase in the availability of nutrients. Biofertilizers with optimal organic matter proportions may be used to produce organic substrates that are more effective and have the potential to be applied as alternatives to soluble NPK fertilizers.